Effect of Growth Temperature on the Lipid and Fatty Acid Composition, and the Dependence on Temperature of Light-induced Redox Reactions of Cytochrome f and of Light Energy Redistribution in the Thermophilic Blue-Green Alga Synechococcus lividus - Fork, David C. (1979)
The thermophilic blue-green alga Synechococcus lividus was grown at 55 and 38 C. Arrhenius plots of the transient reduction of cytochrome during actinic illumination with light that excited both pigment systems revealed breaks near 43 and 26 C for cells grown at 55 C. In cells grown at 38 C these breaks occurred near 37 and 28 C, respectively. The shift from pigment state 1 to state 2 measured by fluorescence transients also showed characteristic breaks in the Arrhenius plots at 44 C for cells grown at 55 C and at 37 to 38 C and possibly at 25 C for cells grown at 38 C. The break points in the Arrhenius plots for the state shift as well as for the cytochrome f reduction are discussed in relation to phase transitions of thylakoid membrane lipids as studied by the temperature dependence of chlorophyll a fluorescence. The variations of fatty acid composition with growth temperature was also studied. When the growth temperature was lowered from 55 to 38 C, the amount of the saturated fatty acid 18:0 in the negatively charged lipids sulfoquinovosyl diglyceride and phosphatidyl glycerol decreased while the unsaturated fatty acids 18:1 and 16:1 increased. In mono- and digalactosyl diglycerides the saturated fatty acids 18:0 and 16:0 decreased and the unsaturated fatty acid 16:1 increased. In general there was an increase in the more fluid lipids in all of the lipid classes when the cells were grown at the lower temperature.